Determining optimal storage time and temperature for the detection of red blood cell and platelet surface associated immunoglobulin by flow cytometry in healthy horses - Frohlich, Miranda (Kansas State University, 2022)
Immune-mediated destruction of red blood cells or platelets is an important consideration when approaching severe anemia or thrombocytopenia, respectively. Differentiating immune-mediated disease from other causes of these cytopenias can be challenging. While the magnitude of decrease in hematocrit or platelet count is helpful, subjectively, this is not always a reliable indicator as other disease processes can also cause marked anemia or thrombocytopenia. A flow cytometric assay used to detect surface-associated immunoglobulin on red blood cells and platelets has been developed to aid in this differentiation in dogs and horses; however, with limited use and a lack of assay standardization. There is a need to standardize assay protocols so that there is consistency between laboratories. It is important for clinicians to understand the results and the possible pre-analytical variables that may affect the reliability of the assay. Currently, there are vast differences in equipment, reagents, sample conditions, and how results are reported. The limited availability of this assay requires samples to be shipped to one of the few reference laboratories equipped to perform it, and there is limited knowledge on how pre-analytical variables, such as the effects of sample storage or shipping conditions, may have on assay performance. Few isolated studies have evaluated the effects of sample storage conditions on the assay results in dogs; however, to the author’s knowledge this has not been assessed in horses. The objective of this study is to identify optimal storage time and temperature of equine whole blood for the detection of red blood cell and platelet surface-associated immunoglobulin concentrations via flow cytometry. Both assays were performed on samples at time of collection (0 hr), and then again at 4, 24, 48, and 72 hours post collection. The red blood cell samples were stored at 4℃ and the platelet samples stored at 4℃ and room temperature.
Keywords: Flow cytometry; Coombs; Red blood cell surface-associated antibody; Platelet surface-associated antibody; Immune mediated hemolytic anemia; Immune mediated thrombocytopenia; Horse